The Objective of Financial Reporting in the Annual Report. - Stone, Donald E. (The Accounting Review, 1967)
This article focuses on the objective of corporate financial reporting and statistical information. Corporate financial and statistical information are communicated to interested users through a wide variety of mediums. However, the published corporate annual report is undoubtedly the most widely distributed comprehensive source of corporate financial data. Two comparatively recent documents suggest some important guidelines and considerations for the formation of a statement of objective for corporate accounting. The American Accounting Association's committee report on the entity concept. In short, the committee advocates a user-oriented approach in defining the entity. They feel this approach to defining the entity places the concept at the very foundation of accounting theory. While the entity concept standing alone may provide only limited guidance in solving such problems, it does provide the theoretical justification for a framework which should prove helpful in solving such problems.